Activation of Invariant Natural Killer T Cells Redirects the Inflammatory Response in Neonatal Sepsis - Bolognese, Alexandra C.; Yang, Weng-Lang; Hansen, Laura W.; Sharma, Archna; Nicastro, Jeffrey M.; Coppa, Gene F.; Wang, Ping (Frontiers in Immunology, 2018)
Sepsis is the third leading cause of death in the neonatal population, due to susceptibility to infection conferred by immaturity of both the innate and adaptive components of the immune system. Invariant natural killer T (iNKT) cells are specialized adaptive immune cells that possess important innate-like characteristics, and have not yet been well-studied in septic neonates. We hypothesized that iNKT cells would play an important role in mediating the neonatal immune response to sepsis. To study this, we subjected five- to seven-day-old neonatal C57BL/6 mice to sepsis by intraperitoneal (i.p.) cecal slurry (CS) injection. Thirty hours prior to or immediately following sepsis induction, pups received i.p. injection of the iNKT stimulator KRN7000 (KRN, 0.2 µg/g) or vehicle. Ten hours after CS injection blood and tissues were collected for various analyses. Thirty-hour pretreatment with KRN resulted in better outcomes in inflammation, lung injury, and survival, while immediate treatment with KRN resulted in worse outcomes compared to vehicle treatment. We further analyzed the activation status of neonatal iNKT cells for 30 hours after KRN administration, and showed a peak in frequency of CD69 expression on iNKT cells and serum IFN-γ levels at 5 and 10 hours, respectively. We then used CD1d knockout (KO) neonatal mice to demonstrate that KRN acts through the MHC-like molecule CD1d to improve outcomes in neonatal sepsis. Finally, we identified that KRN pretreatment exerts its protective effect by increasing systemic levels of TGF-β1. These findings support the importance of iNKT cells for prophylactic immunomodulation in neonates susceptible to sepsis.